The impact of sleep quality on the mental health of a non-clinical population - João, Karine Alexandra Del Rio; Jesus, Saul Neves de; Carmo, Cláudia; Pinto, Patrícia (Sleep medicine, 2018)
Sleep quality relates to mental health in clinical and non-clinical populations. However, there is more evidence of this relationship in clinical populations. Therefore, there is lack of evidence on how these variables relate and on which sociodemographic factors influence this relationship in non-clinical populations. In this study we hypothesize that in a non-clinical population sleep quality predicts mental health indicators and that age, country and gender moderate this relationship. In a sample of 1552 subjects from Portugal, Spain and Brazil, self-reported sleep quality and mental health indicators were assessed through the Pittsburgh Sleep Quality Index and the Depression, Anxiety and Stress Scale-21, respectively. A multivariate linear regression model was used to test the research hypotheses. This adjusted model explained 10.1%, 12.3% and 13.1% of the variability of Depression, Anxiety and Stress, respectively, suggesting multiple sources of variance. Our results confirmed that sleep quality predicts mental health in non-clinical populations, and that the variable country is a significant moderator of this relationship. •We hypothesize that sleep quality predicts mental health in non-clinical populations.•We propose that age, gender and country moderate the relationship between sleep quality and mental health.•The PSQI and the DASS-21 assess sleep quality and mental health respectively.•Sleep quality predicts mental health in non-clinical populations.•“Country” is a significant moderator of this relationship.